APPLICATIONS OF ARTIFICIAL INTELLIGENCE IN THE PHARMACEUTICAL INDUSTRY - Vama Sharma; Dr. Mahesh Kumar Sharma (International Educational Journal of Science and Engineering, 2025)
The pharmaceutical sector is experiencing a significant transformation due to the incorporation of artificial intelligence (AI) technologies throughout the entire drug development process. This review analyses the existing applications, emerging trends, and future possibilities of AI within pharmaceutical research and development. AI is changing traditional methods by improving efficiency, cutting costs, and speeding up the time for new therapeutics to reach the market, affecting everything from drug discovery and clinical trials to manufacturing and post-market surveillance. This paper offers a detailed exploration of AI applications in the pharmaceutical industry, emphasizing key technologies, challenges, and potential opportunities that lie ahead.